Calculation of Proton range in Some Organic Compounds Energies (1000-100000)keV (Global Journal of Science Frontier Research, 2014)
Theoretical study have been done to calculated the Range for protons in ten organic compounds which is: [ polypropylene(C 3 H 6 ) ,Polycarbonate (C 16 H 14 O 3 ), Mylar (C 10 H 8 O 4 ), Polyvinylalcohol (C 2 H 4 O), Polyoxymethylene (CH 2 O), by using SRIM2013 program written by Mathlab language. the range calculated to protons for energy (1000-100000) keV , by using fitting equations and the semi empirical equation (Devise two equation), and we calculated the rate error and correlation coefficient betweenRange(SRIM) and Range(semi-emp) as seen in tables by using Excel program. The results are agreed with the SRIM 2013 program, so our results showed to be good.
Keywords: proton Range; organic compound